Long-term efficacy and safety of sapropterin in patients who initiated sapropterin at < 4 years of age with phenylketonuria: results of the 3-year extension of the SPARK open-label, multicentre, randomised phase IIIb trial - Ania C. Muntau (Orphanet Journal of Rare Diseases, 2021)
Abstract Background During the initial 26-week SPARK (Safety Paediatric efficAcy phaRmacokinetic with Kuvan®) study, addition of sapropterin dihydrochloride (Kuvan®; a synthetic formulation of the natural cofactor for phenylalanine hydroxylase, tetrahydrobiopterin; BH4), to a phenylalanine (Phe)-restricted diet, led to a significant improvement in Phe tolerance versus a Phe-restricted diet alone in patients aged 0–4 years with BH4-responsive phenylketonuria (PKU) or mild hyperphenylalaninaemia (HPA). Based on these results, the approved indication for sapropterin in Europe was expanded to include patients < 4 years of age. Herein, we present results of the SPARK extension study (NCT01376908), evaluating the long-term safety, dietary Phe tolerance, blood Phe concentrations and neurodevelopmental outcomes in patients < 4 years of age at randomisation, over an additional 36 months of treatment with sapropterin. Results All 51 patients who completed the 26-week SPARK study period entered the extension period. Patients who were previously treated with a Phe-restricted diet only (‘sapropterin extension’ group; n = 26), were initiated on sapropterin at 10 mg/kg/day, which could be increased up to 20 mg/kg/day. Patients previously treated with sapropterin plus Phe-restricted diet, remained on this regimen in the extension period (‘sapropterin continuous’ group; n = 25). Dietary Phe tolerance increased significantly at the end of the study versus baseline (week 0), by 38.7 mg/kg/day in the ‘sapropterin continuous’ group (95% CI 28.9, 48.6; p < 0.0001). In the ‘sapropterin extension’ group, a less pronounced effect was observed, with significant differences versus baseline (week 27) only observed between months 9 and 21; dietary Phe tolerance at the end of study increased by 5.5 mg/kg/day versus baseline (95% CI − 2.8, 13.8; p = 0.1929). Patients in both groups had normal neuromotor development and growth parameters. Conclusions Long-term treatment with sapropterin plus a Phe-restricted diet in patients who initiated sapropterin at < 4 years of age with BH4-responsive PKU or mild HPA maintained improvements in dietary Phe tolerance over 3.5 years. These results continue to support the favourable risk/benefit profile for sapropterin in paediatric patients (< 4 years of age) with BH4-responsive PKU. Frequent monitoring of blood Phe levels and careful titration of dietary Phe intake to ensure adequate levels of protein intake is necessary to optimise the benefits of sapropterin treatment. Trial registration ClinicalTrials.gov, NCT01376908. Registered 17 June 2011, https://clinicaltrials.gov/ct2/show/NCT01376908 .